Skin manifestations after immunisation with an adjuvanted recombinant zoster vaccine, Germany, 2020 - Orru', Stefano; Bierbaum, Sibylle; Enk, Alexander; Hengel, Hartmut; Hoffelner, Marcus; Huzly, Daniela; Keller-Stanislawski, Brigitte; Mahler, Vera; Mockenhaupt, Maja; Oberle, Doris Franziska (Eurosurveillance, 2023)
Background Shortly after the launch of a novel adjuvanted recombinant zoster vaccine (RZV), Shingrix, cases of suspected herpes zoster (HZ) or zoster-like skin reactions following immunisation were reported. Aim We aimed to investigate if these skin manifestations after administration of RZV could be HZ. Methods Between April and October 2020, general practitioners (GP) reporting a suspected case of HZ or zoster-like skin manifestation after RZV vaccination to the Paul-Ehrlich-Institut, the German national competent authority, were invited to participate in the study. The GP took a sample of the skin manifestation, photographed it and collected patient information on RZV vaccination and the suspected adverse event. We analysed all samples by PCR for varicella-zoster virus (VZV) and herpes-simplex virus (HSV) and genotyped VZV-positive samples. In addition, cases were independently assessed by two dermatologists. Results Eighty eligible cases were enrolled and 72 could be included in the analysis. Of the 72 cases, 45 were female, 33 were 60-69 years old, 32 had skin symptoms in the thoracic and 27 in the cervical dermatomes. Twenty-seven samples tested PCR positive for VZV (all genotyped as wild-type, WT), three for HSV-1 and five for HSV-2. Conclusion It may be difficult to distinguish HZ, without a PCR result, from other zoster-like manifestations. In this study, VZV-PCR positive dermatomal eruptions occurring in the first weeks after immunisation with RZV were due to WT VZV, which is not unexpected as HZ is a common disease against which the vaccine is unlikely to provide full protection at this time.